Research Progress on Localization of Pulmonary Nodules - Wang, Jiangnan; Yan, Weiya; Ding, Xuebing (Zhongguo yi liao qi xie za zhi, 2024)
With the widespread adoption of low-dose computed tomography (LDCT) and advancements in computed tomography image resolution, the detection rate of pulmonary nodules, especially smaller ones, has significantly improved. The risk of developing malignant tumors increases with the pulmonary nodule diameter. Video-assisted thoracoscopic surgery (VATS) stands out as the preferred surgical method. The accurate localization of pulmonary nodules is crucial for the success of VATS and remains a significant challenge for thoracic surgeons. Currently, commonly employed localization methods include CT-guided percutaneous positioning, bronchoscope-guided positioning, intraoperative ultrasound positioning, augmented reality (AR), and 3D print-assisted positioning. This review explores recent research progress, highlights the strengths and weaknesses of various pulmonary nodule localization methods. The aim is to provide valuable insights for clinical applications and guide future developments in this field.